2020
DOI: 10.2196/18811
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting COVID-19 and Virtual Care Trends: Cohort Study

Abstract: Background The coronavirus disease (COVID-19) pandemic is rapidly spreading across the world. As of March 26, 2020, there are more than 500,000 cases and more than 25,000 deaths related to COVID-19, and the numbers are increasing by the hour. Objective The aim of this study was to explore the trends in confirmed COVID-19 cases in North Carolina, and to understand patterns in virtual visits related to symptoms of COVID-19. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 6 publications
1
98
0
4
Order By: Relevance
“…Thanks to both positive evidence from previous epidemics/pandemics and technological advancements, during this critical period, the use of telemedicine has increased, especially in industrialized countries, mostly the United States [ 13 ], the United Kingdom, and China [ 14 , 15 ].…”
Section: The Importance Of Telemedicine In a Pandemicmentioning
confidence: 99%
“…Thanks to both positive evidence from previous epidemics/pandemics and technological advancements, during this critical period, the use of telemedicine has increased, especially in industrialized countries, mostly the United States [ 13 ], the United Kingdom, and China [ 14 , 15 ].…”
Section: The Importance Of Telemedicine In a Pandemicmentioning
confidence: 99%
“…A study in the US noticed an increase of COVID-19 cases within areas that included a major airport, 15 suggesting travel hubs are important sources of spreading. Studies on the US and UK concluded that introducing social distancing regulations reduced contact rate and physical proximity to others, resulting in reductions in COVID-19 incidence rates.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…New digital technologies (i.e., eHealth) are emerging rapidly in health care to promote patients' self-management and engagement and improve patient-centred cancer care [8]. The interest in remote care delivery by eHealth has increased even more during the current COVID-19 pandemic, as remote consultation decreases the risk of spreading the virus and could decrease the pressure on health care resources [9,10]. Additionally, eHealth is used to remotely monitor patients' postoperative recovery in surgical wards or at home after hospital discharge [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Also, eHealth literacy is known to be lower among older adults with cancer compared with their younger counterparts [18]. The COVID-19 pandemic has further increased the need for new digital solutions in health care and clinical research [9,10]. It is thus of the utmost importance to identify barriers to participation in clinical eHealth trials among the older population.…”
Section: Introductionmentioning
confidence: 99%